Clinical Characteristics of Paediatric Hyperinflammatory Syndrome in the Era of Corona Virus Disease 2019 (COVID-19) - Basu, Manjari (Indian J Clin Biochem, 2021)
The pandemic of COVID-19 initially appeared to cause only a mild illness in children. However, it is now apparent that a small percentage of children can develop a hyperinflammatory syndrome labeled as Pediatric inflammatory multisystem syndrome—temporally associated with SARS-CoV-2 (PIMS-TS) with a phenotype resembling Kawasaki disease (KD) ('Kawa-COVID-19′). Features of this newly recognized condition may include fever, hypotension, severe abdominal pain and cardiac dysfunction, evidence of inflammation, and single or multi organ dysfunction in the absence of other known infections. Children emerge to have mild symptoms compared to adults, perhaps due to reduced expression of the angiotensin converting enzyme (ACE)-2 receptor (the target of SARS-CoV-2) gene, trained innate immunity, and a young and fit immune system. Some of these children may share features of Kawasaki disease, toxic shock syndrome or cytokine storm syndrome. They can deteriorate rapidly and may need intensive care support as well. The PCR test is more often negative although most of the children have antibodies to SARS-CoV-2. Although the pathogenesis is not clearly known, immune-mediated injury has been implicated.